Appropriateness of antibiotic prescriptions for acute sinusitis and pharyngitis in an integrated healthcare system. (29th May 2018) - Chauhan, Lakshmi; Young, Heather; Knepper, Bryan C.; Shihadeh, Katherine C.; Jenkins, Timothy C.
Abstract: We evaluated the appropriateness of antibiotic prescriptions for acute sinusitis and pharyngitis. Overall, 81% of antibiotic prescriptions for acute sinusitis were inappropriate and 48% of antibiotic prescriptions for pharyngitis were inappropriate. Types of prescribing errors differed between the 2 infections, including lack of an indication for antibiotics and excessive duration in 50% of sinusitis cases and incorrect antibiotic dose in 33% of pharyngitis cases. Infect Control Hosp Epidemiol 2018;0, 1–3